Student performance and loss aversion - Heiko Karle; Dirk Engelmann; Martin Peitz (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2019)
In this paper, we match data on student performance in a multiple-choice exam with data on student risk preferences that are extracted from a classroom experiment. We find that more-loss-averse students leave more questions unanswered and perform worse in the multiple-choice exam when giving an incorrect answer is penalized compared to not answering. We provide evidence that loss aversion parameters extracted from lottery choices in a controlled experiment have predictive power in a field environment of decision making under uncertainty. Furthermore, the degree of loss aversion appears to be persistent over time, as the experiment was conducted three months prior to the exam. We also find important differences across genders; they are partly explained by differences in loss aversion.
Keywords: C91; D01; D11; D83; 330; Loss Aversion; Decision Making under Uncertainty; Multiple Choice